Study of Performance of Eighth Grade Students in Fars Province in Cognitive and Content Domains in Mathematics by TIMSS 2019 Assessment Results - Amir Peyravi; Mohammad Reza Kazemi (ریاضی و جامعه, 2023)
In this paper, we analyze the eighth grade students performance in Fars province in cognitive and content domains in mathematics by TIMSS 2019 assessment results. Due to the cultural, social and economic proximity of Fars and Isfahan provinces, corresponding results have been obtained for students of Isfahan province and comparisons have been made in each domain by using appropriate tests. Also, gender analysis has been derived in both cognitive and content dimensions and in all of their domains in mathematics for students of both provinces